The Underlying Causes of Immigration from Mexico to the United States: Structures of Deprivation - Del Regil Castilla, Álvaro (Revista Internacional de Salarios Dignos, 2019)
This paper focuses on the underlying causes of immigration from Mexico to the United States from a political and socio- economic viewpoint. However, the root causes behind the flows of emigrants in other regions of the world are consistently the same. They result from the impact of powerful geo- political interests on the general population of both the emitting and the receiving countries of the millions of migrants in their escape from unbearable conditions and in pursuit of a dignified life. From this perspective, we will uncover and review the underlying causes of immigration from Mexico to the US, which are structural, in an effort to shed light onto their real solution. That is, the only way to permanently solve the issue of Mexican migration to the US, is by addressing the structural causes that force people to leave their homelands. Addressing only the symptoms triggered by these causes will never solve the issue and instead would further consolidate the patterns regardless of how aggressive and inhumane the policies are designed to stop the flows of migrants. We also focus on Mexico because it has been for many decades the main source of immigrants to the US due to its proximity and even more so after the North American Free Trade Agreement (NAFTA) in 1994, which has made Mexico the third largest US trading partner, after China and Canada, beyond being the main exporter of migrants forced to leave their communities.